Exploring positions 6 and 7 of a quinazoline-based scaffold leads to changes in selectivity and potency towards RIPK2/3 kinases - Misehe, Mbilo; Matoušová, Marika; Dvořáková, Alexandra; Hercík, Kamil; Škach, Kryštof; Chalupská, Dominika; Dejmek, Milan; Šála, Michal; Hájek, Miroslav; Boura, Evzen; Mertlíková-Kaiserová, Helena; Nencka, Radim (European journal of medicinal chemistry, 2023)
Receptor-interacting protein kinases 2 and 3 (RIPK2 and RIPK3) are considered attractive therapeutic enzyme targets for the treatment of a multitude of inflammatory diseases and cancers. In this study, we developed three interrelated series of novel quinazoline-based derivatives to investigate the effects of extensive modifications of positions 6 and 7 of the central core on the inhibitory activity and the selectivity against these RIPKs. The design of the derivatives was inspired by analyses of available literary knowledge on both RIPK2 and RIPK3 in complex with known quinazoline or quinoline inhibitors. Enzymatic investigations for bioactivity of the prepared molecules against purified RIPKs (RIPK1-4) shed light on multiple potent and selective RIPK2 and dual RIPK2/3 inhibitors. Furthermore, evaluations in living cells against the RIPK2-NOD1/2-mediated signaling pathways, identified as the potential primary targets, demonstrated nanomolar inhibition for a majority of the compounds. In addition, we have demonstrated overall good stability of various lead inhibitors in both human and mouse microsomes and plasma. Several of these compounds also were evaluated for selectivity across 58 human kinases other than RIPKs, exhibiting outstanding specificity profiles. We have thus clearly demonstrated that tuning appropriate substitutions at positions 6 and 7 of the developed quinazoline derivatives may lead to interesting potency and specificities against RIPK2 and RIPK3. This knowledge might therefore be employed for the targeted preparation of new, highly potent and selective tools against these RIPKs, which could be of utility in biological and clinical research.
Keywords: chinazoliny; RIPK2; myši; Animals; Quinazoline derivatives; Quinazolines; RIPK3; zvířata; Humans; Mice; Inflammation; Kinase inhibitor; NOD; Receptor-Interacting Protein Serine-Threonine Kinase 2; Microsomes; lidé; mikrozomy; protein-serin-threoninkinasa 2 interagující s receptory